Cytotoxic Evaluation of Doxorubicin Combination with Baicalein and Resveratrol Against Hct116 and Hepg2 Cancer Cell Lines (Conference Paper) # - Shniakat, Wafa Naji; Ekbal H. Al-Khateeb, Ekbal H.; Numan, Nawfal A.M.; Manal M. Abbas; Shakya, Ashok (Iraqi Journal of Pharmaceutical Sciences, 2023)
Combination of natural poly-phenolic compounds with chemotherapeutic agents is recently being a novel strategy in cancer therapy researches owing to their potential antioxidant and anti-inflammatory properties that modulate several intracellular signaling pathways.Resveratrol and Baicalein are well known poly-phenolic compounds that belong to stilbene and flavone subclasses, respectively.This study aims to investigate the possible enhancement effect of resveratrol and Baicalein when combined with doxorubicin using a different combination ratio and applied on two cancer cell lines: HCT116 (colorectal cancer cells) and HepG2 (hepatocellular cancer cells). It also investigates the possibility of such natural compounds to provide a protection effect on cardiocytes (H9C2) when resveratrol and Baicalein treatment followed by doxorubicin is used. The two cancer cell lines were treated with different combination groups, including the combination between doxorubicin and Baicalein or resveratrol and the combination between the three compounds using a different combination ratio for both treatment groups (i.e., two drugs or three drugs combination). Treatment applied on cells, using cell density of 7000 cells /well and incubation time was 48 hrs. MTT test was performed to assay the cell viability.The results obtained showed that the cytotoxicity of doxorubicin in the two cancer cell lines has increased when combined with Baicalein and resveratrol. Doxorubicin IC50 decreased from 4.99 µg/ml to 0.3657 µg/ml and from 7.3 µg/ml to 0.676 µg/ml on HCT116 and HepG2 cells, respectively, using constant combination ratio (1:1:1).The combination of doxorubicin, Baicalein, and resveratrol has resulted in a less cardiotoxic effect compared to treatment with doxorubicin alone. This decrease was obviously seen when the three compounds were combined using a low concentration range and with a constant combination ratio.Conclusion: combinations of Baicalein and resveratrol with doxorubicin chemotherapeutic drug In Vitro had enhanced the cytotoxic activity of such a chemotherapeutic drug, while simultaneously eliminating its cardio-toxicity side effect.